Preparation and characterization of gel polymer electrolytes using poly(ionic liquids) and high lithium salt concentration ionic liquids. Issue 45 (8th November 2017) - Wang, Xiaoen; Zhu, Haijin; Girard, Gaetan M. A.; Yunis, Ruhamah; MacFarlane, Douglas R.; Mecerreyes, David; Bhattacharyya, Aninda J.; Howlett, Patrick C.; Forsyth, Maria
Abstract : Poly(ionic liquids)-based gel polymer electrolytes containing high lithium salt concentration ionic liquids are demonstrated. Abstract : Polymerized ionic liquids or poly(ionic liquids) (polyILs) have been considered as promising hosts for fabrication of gel polymer electrolytes (GPEs) containing ionic liquids. In this work, a novel GPE based on a polyIL, poly(diallyldimethylammonium) bis(trifluoromethanesulfonyl)imide (PDADMA TFSI), and a high lithium-concentration phosphonium ionic liquid, trimethyl(isobutyl)phosphonium bis(fluorosulfonyl)imide (P111i4 FSI), is prepared. The composition-dependent behaviour of the GPEs is investigated by differential scanning calorimetry (DSC), electrochemical impedance spectroscopy (EIS) and solid-state nuclear magnetic resonance (solid-state NMR). The effects of Al2 O3 nano-particles on the polymer electrolyte properties are also discussed. It is shown that the introduction of high lithium-concentration ionic liquids into the polyIL can effectively decrease the glass transition temperature ( T g ) of the resulting GPE, leading to improved ion dynamics and higher ionic conductivity. The Al2 O3 nano-particles effectively enhanced the mechanical stability of the GPEs. Most importantly, although adding PDADMA TFSI to the ionic liquids decreases the diffusion coefficient of both Li + and anions, a greater decrease in the anion diffusion is observed, resulting in a higher Li + transport number (as evaluated by NMR) than that seen in the original ILs. Finally, a highly conductive free-standing GPE membrane is fabricated, and extremely stable lithium symmetrical cell performance is demonstrated.